Developing Suplementry Speaking Material in Digital Media - Yulfi Yulfi; Syaprizal Syaprizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research was to develope and validate the suplementary speaking material in digital media for accounting students of SMK Negeri 1 Lubuklinggau. This research used Research and Development Method by applying Borg and Gall Model. There were ten steps, they are (1) research and information collecting (2) planning (3) developing preliminary form of product (4) preliminary field testing (5) main product revision (6) field testing (7) operational product revision (8) operational field testing (9) final product (10) dissemination and implementation.. The subjects were the Accounting students of eleventh grade in academic year 2020/2021. While, for step 6, 8 and 10 were applied by using Google Classroom application in English group of XI Accounting Program. The data showed that there were some problem faced by the students aespecially in finding a speaking book which concerning to accounting program. The teacher also need a book that can help English speaking skill not only for general English. After following the ten steps in R&D method, started from analyzing, evaluating, revising and trying out, it was concluded that the suplementary speaking material in digital media for accounting students can help them in learning English based on their need. It was proven by the average score of questionnaire (4.35) with very good criteria. Keywords: Developing, Supplementary Speaking Materials, Accounting Students